Interstitial cells of Cajal mediate inhibitory neurotransmission in the stomach. - Burns, A J (1996)
The structural relationships between interstitial cells of Cajal (ICC), varicose nerve fibers, and smooth muscle cells in the gastrointestinal tract have led to the suggestion that ICC may be involved in or mediate enteric neurotransmission. We characterized the distribution of ICC in the murine stomach and found two distinct classes on the basis of morphology and immunoreactivity to antibodies against c-Kit receptors. ICC with multiple processes formed a network in the myenteric plexus region from corpus to pylorus. Spindle-shaped ICC were found within the circular and longitudinal muscle layers (IC-IM) throughout the stomach. The density of these cells was greatest in the proximal stomach. IC-IM ran along nerve fibers and were closely associated with nerve terminals and adjacent smooth muscle cells. IC-IM failed to develop in mice with mutations in c-kit. Therefore, we used W/W(V) mutants to test whether IC-IM mediate neural inputs in muscles of the gastric fundus. The distribution of inhibitory nerves in the stomachs of c-kit mutants was normal, but NO-dependent inhibitory neuro-regulation was greatly reduced. Smooth muscle tissues of W/W(V) mutants relaxed in response to exogenous sodium nitroprusside, but the membrane potential effects of sodium nitroprusside were attenuated. These data suggest that IC-IM play a critical serial role in NO-dependent neurotransmission: the cellular mechanism(s) responsible for transducing NO into electrical responses may be expressed in IC-IM. Loss of these cells causes loss of electrical responsiveness and greatly reduces responses to nitrergic nerve stimulation.